Pendidikan Islam Modern: Kurikulum PAI Berbasis Al-Qur’an, Sunnah, dan Budaya Sesuai Kebutuhan Masyarakat - Achmad Junaedi Sitika; Zia Achmalia Adela; Ega Najwa Ismail; Titik Ayu Kartika (Hidayah : Cendekia Pendidikan Islam dan Hukum Syariah, 2025)
The creation of an Islamic Religious Education (PAI) curriculum grounded in the Qur'an, Sunnah, and culture is covered in this study. This curriculum emphasizes the spread of religious knowledge while also incorporating relevant cultural values ​​to provide pupils a more meaningful and contextual education. The goal of this curriculum is to develop pupils who are honorable, tolerant, and capable of adjusting to the problems of the world without abandoning or forgetting their cultural and religious values. To address these issues, a qualitative method known as the literature review method or literature study was used in this study. Books, journal articles, and other materials relating to Islamic education, cultural values, and curriculum development methodologies are among the scientific research and literature that serve as its reference sources. According to this study, students' understanding of Islamic teachings that are applicable to their daily lives may be strengthened by incorporating cultural values ​​into the curriculum. Teachers have a critical role in creating education that integrates religious and cultural values ​​in order to produce a generation that is morally upright, open-minded, and prepared to deal with the changing dynamics of society.